2010
DOI: 10.1007/s12564-010-9078-0
|View full text |Cite
|
Sign up to set email alerts
|

University students’ perceptions of a holistic care course through cooperative learning: implications for instructors and researchers

Abstract: The benefits of cooperative learning have been advocated in a wide range of educational contexts in higher education. There is, however, rare information on the contributions of holistic education courses on college students. Using grounded theory methods, this preliminary study was to explore participants' perceptions of a holistic care course through cooperative learning. The results indicated that five primary categories including learning environment construction, multiple learning processes, cognitive cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 12 publications
3
23
0
2
Order By: Relevance
“…First, learning self-efficacy increases engagement in a learning context. Individuals with a high level of learning self-efficacy tend to be actively involved in development and learning activities that often force them to explore new terrain (Pan et al, 2010). For example, Bouffard-Bouchard (1990) found that students with high levels of self-efficacy worked more practice problems than did those with low levels of self-efficacy.…”
Section: Self-efficacy and Learning B-skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, learning self-efficacy increases engagement in a learning context. Individuals with a high level of learning self-efficacy tend to be actively involved in development and learning activities that often force them to explore new terrain (Pan et al, 2010). For example, Bouffard-Bouchard (1990) found that students with high levels of self-efficacy worked more practice problems than did those with low levels of self-efficacy.…”
Section: Self-efficacy and Learning B-skillsmentioning
confidence: 99%
“…Noe and Wilk (1993) presented that individuals with higher levels of self-efficacy are more likely to have a positive attitude toward learning, a belief that there are benefits to be gained from participation in such activities, and a greater awareness of their specific development needs. Pan et al (2010) also argued that individuals with high levels of learning self-efficacy are better able to cope with the stress involved in personal learning because they believe they can influence things in order to overcome obstacles in the learning process. In contrast, when encountering challenging (or even threatening) learning situations, people with low levels of learning self-efficacy tend to give up easily, attribute failure to themselves, and experience high levels of anxiety and/or depression (Bandura, 1986).…”
Section: Self-efficacy and Learning B-skillsmentioning
confidence: 99%
“…Entre estas competencias destacan: el desarrollo de la capacidad crítica de los y las estudiantes (Escribano González, 1995), la creación de liderazgo y la mejora de la capacidad de comunicación (Domingo, 2008), la mejora en al autoeficacia (Cannon y Scharmann, 1996), el desarrollo de una actitud solidaria (Traver Martí y García López, 2006), la creación de un conocimiento holístico (Pan, Pan, Lee, y Chang, 2010) y la mejora de la disciplina y el compromiso de los y las estudiantes (Learreta Ramos, 2005).…”
Section: La Planificación De La Responsabilidad Y Las Interacciones Aunclassified
“…For example, very few empirical studies have focused on students' perceptions and experiences of holistic education in higher education (Ting, Pan, & Yang, 2008). Pan and his colleagues (Pan, Pan, Lee, & Chang, 2010;Pan & Wei, 2006) developed a qualitative method for investigating students' holistic education. However, they point out as one of their research limitations that holistic education needs to be examined through quantitative methods (Pan et al, 2010).…”
mentioning
confidence: 99%